Development and external validation of a prediction model for survival in patients with resected ampullary adenocarcinoma. Issue 9 (September 2020) - Moekotte, Alma L.; van Roessel, Stijn; Malleo, Giuseppe; Rajak, Rushda; Ecker, Brett L.; Fontana, Martina; Han, Ho-Seong; Rabie, Mohamed; Roberts, Keith J.; Khalil, Khalid; White, Steven A.; Robinson, Stuart; et al.
Abstract: Introduction: Ampullary adenocarcinoma (AAC) is a rare malignancy with great morphological heterogeneity, which complicates the prediction of survival and, therefore, clinical decision-making. The aim of this study was to develop and externally validate a prediction model for survival after resection of AAC. Materials and methods: An international multicenter cohort study was conducted, including patients who underwent pancreatoduodenectomy for AAC (2006–2017) from 27 centers in 10 countries spanning three continents. A derivation and validation cohort were separately collected. Predictors were selected from the derivation cohort using a LASSO Cox proportional hazards model. A nomogram was created based on shrunk coefficients. Model performance was assessed in the derivation cohort and subsequently in the validation cohort, by calibration plots and Uno's C-statistic. Four risk groups were created based on quartiles of the nomogram score. Results: Overall, 1007 patients were available for development of the model. Predictors in the final Cox model included age, resection margin, tumor differentiation, pathological T stage and N stage (8th AJCC edition). Internal cross-validation demonstrated a C-statistic of 0.75 (95% CI 0.73–0.77). External validation in a cohort of 462 patients demonstrated a C-statistic of 0.77 (95% CI 0.73–0.81). A nomogram for the prediction of 3- and 5-year survival was created. The four risk groups showed significantly different 5-year survival rates (81%, 57%, 22% and 14%, p < 0.001). Only in the very-high risk group was adjuvant chemotherapy associated with an improved overall survival. Conclusion: A prediction model for survival after curative resection of AAC was developed and externally validated. The model is easily available online via www.pancreascalculator.com. Highlights: A prediction model for survival after resection of ampullary adenocarcinoma was created The model was externally validated with a C-statistic of 0.77 The model may be used to predict 3- and 5-year overall survival in individual patients Four risk groups were created with statistically significant differences in survival Only in the very high risk group was adjuvant chemotherapy associated with an improved overall survival